The Chronicles of Kunene: The Lion, the Omuhimba and the Drone - (:unkn) unknown (My University, 2022)
Many technology projects are driven by (hidden) agendas which prioritize the one or the other stakeholder or the technology itself, thereby creating tensions and compromising important perspectives. In the field of digital conservation and wildlife management, the focus has often been on safeguarding wildlife (the lion), not incorporating socio-economic factors of communities (the Omuhimba), by exploiting technologies concerned with wildlife data collection only (the drone). Concerned with reconciling heterogeneous perspectives the authors present the development and conceptualisation of an integrated wildlife monitoring system in Southern Africa. The authors postulate that a community-based co-design approach, grounded in the Ubuntu philosophy, leads to novel and innovative technology designs embracing ecocentrism.
Keywords: African Research